Thermal conductivity of powder injection molded carbon nanotube-reinforced copper-matrix composites - Muhsan, A.S. (American Powder Metallurgy Institute, 2015)
A new fabrication method for carbon nanotube (CNT)-reinforced copper-matrix composites is presented. The combination of a nanoscale dispersion of functionalized CNTs in a low-viscosity paraffin wax under sonication treatment followed by powder injection molding (PIM) was carried out. The CNT content in the copper matrix was varied from 0 to 10 vol.. Evidence for the existence of functional groups and microstructural analyses of the composites are presented utilizing Fourier transformed infrared spectroscopy (FTIR), transmission electron microscope (TEM), and energy dispersive spectroscopy (EDS). Field emission electron microscope (FESEM) and TEM observations confirm an excellent dispersion of CNTs in the copper matrix and bonding integrity between copper particles and individual CNTs. FTIR spectroscopy identified functional groups on the outer surface of individual CNTs; these provide electrostatic repulsive forces that help in overcoming the van der Waal's forces and hence improve dispersion of the CNTs. The increase in thermal conductivity of the copper-CNT composites was directly proportional to the increase in sintering temperature and CNT content. Adding 10 vol. of function-alized CNTs resulted in a significant increase in thermal conductivity up to 581 W/mÂ·K; this corresponds to an increase of 76 and 16.2, compared with pure sintered copper and the theoretically predicted level, respectively.